IMPROVING SUMMARY QUALITY USING SUMMARIZING STRATEGIES FROM MULTIPLE SOURCE TEXTS - Nurul Aryanti; Muhammad Nadjmuddin (HOLISTICS, 2015)
The aim of this study was to examine students’ summarizing strategies in writing summaries from multiple texts. A total of 30 students from the group of high-ability and low-ability based on TOEIC scores were invited to participate in this study for data collection using writing summary task. The participants were taught summary writing using concept mapping strategies. The summarizing strategies of the students were collected through think aloud protocol and questionnaire. This study suggests that explicit instruction in the use of concept mapping strategies during summarizing was crucial to improve the quality of their summaries. This study indicates some differences in the strategies employed by the students of the two different groups. Information about successful strategies employed by high ability students in writing a summary can be used to teach low ability students.